Pengembangan Aplikasi Tracer Study Berbasis Android - Muzakki, M Saidul (Program Studi Pendidikan Islam Anak Usia Dini, Fakultas Ilmu Tarbiyah dan Keguruan, UIN Sunan Kalijaga, Yogyakarta, 2016)
Tracer study is a study of graduates trace and it aims to determine educational outcomes in the form of transition from education to the world of work. Tracer study could also provide information for the importance of evaluation of higher education result for improvement towards better quality. This research is Research and Development (R&D) research. The Model that developed is D+D (Design and Development). Product specification that is expected is tracer study application which can run on mobile phones based on android. Media experts validation result shows that in general the android-based tracer application product has a good assessment. Namely the assessment of all aspect of the interface, program consistency, level of difficulty, functioning hyperlink, and interactive has good score.